Keupayaan mengajar guru-guru Bahasa Melayu sekolah menengah - Shaari, Abdull Sukor; Yaakub, Noran Fauziah; Awang Hashim, Rosna (UUM College of Arts and Sciences, 2004)
Teaching ability is one of the predictors for teacher performance. Two important dimensions for teaching ability are content knowledge and pedagogical content knowledge of teachers. The purposes of this study are (1)to examine teaching ability of Bahasa Melayu teachers in secondary school and (2) to compare teaching ability according to gender; academic qualifications and teaching experience. This correlational study used a total of 370 Bahasa Melayu teachers from 108 secondary schools in Kedah. Results indicated that most of the respondents have high teaching ability but there are significant differences in teaching ability according to gender, age, academic qualifications and teaching experience.